The development of sets-based chemic media on hydrocarbon material - Meli Sartika Silaban; Selly Aprilia Nisa; Saronom Silaban; Julinton Sianturi (Jurnal Pendidikan Kimia (JPKim), 2022)
Learning media is a tool that is inseparable from the learning process in the world of education, especially in the current era of the media world which is increasingly utilizing media innovation. This research is a development research that aims to develop hydrocarbon chemical media. The development method used is ADDIE (Analysis, Design, Development, Implementation, Evaluation) which is modified by the researcher so that in this development research, only four stages are carried out, namely analysis, design, development and evaluation. The validation of the developed hydrocarbon chemical media was managed on a Likert scale of 1-4 by five expert validators, namely chemistry lecturers and teachers. The results of the analysis from the validation by expert validators on the feasibility of hydrocarbon chemical media according to the BSNP (National Education Standards Agency) modified with SETS eligibility are the content feasibility aspect of 3.58 (89.50 %); language feasibility aspect 3.68 (92.00%); presentation feasibility aspect 3.49 (87.25%); aspects of the feasibility of graphics 3.41 (85.25%); the feasibility aspect of implementing SETS 3.41 (85.25%). The average score of validation by the five validators is 3.54 with valid criteria and a presentation of 86.80% in a very feasible category. Based on the results of the validation of the hisrocarbon chemic media, it was concluded that the hydrocarbon chemical media was in accordance with the feasibility of the BSNP (National Education Standards Agency) modified with SETS eligibility and showed that the SETS-based hydrocarbon chemic media (chemistry comic) was very suitable to be used as a learning medium on hydrocarbon material.Keywords:ADDIE model, Chemistry comic, Hydrocarbons, SETS